Serum and Urinary Levels of Nitric Oxide and Uric Acid in Nigerian Children with Asthma (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Asthma is associated with increased production of reactive oxygen and nitrogen species and an alteration in the levels of antioxidants activities in the lung and blood. The increased production of the superoxide anion radicals contributes to airway remodelling and disease severity. Physiologically, the effect of increased free radical generation is eliminated by corresponding activities of a network of antioxidants. Presently, there is the dearth of information on the steady-state concentrations of nitric oxide (NO) and uric acid (UA) in children with asthma. The serum and urinary levels of NO and UA in children with asthma were thus determined in this study. Methodology: Fifty children consisting of 25 children with asthma and 25 age-matched apparently healthy children without asthma were enrolled into this study. Serum and urinary levels of NO and UA were determined using standard methods. Results: Serum levels of NO and UA were significantly higher while the urinary levels of NO and UA were significantly lower in children with asthma compared with the controls. There was no significant correlation between the serum ad urinary levels of NO and UA in children with asthma. Also, gender differences were not observed in the serum and urinary levels of NO and UA in children with asthma. Conclusion: Children with asthma have elevated serum levels of NO and UA accompanied with suboptimal urinary excretion. Therefore, children with asthma might benefit from routine renal function assessment owing to damages that can result from systemic accumulation of UA with concomitant reduction in its urinary excretion.